المستشرقون ونشأة التصوف - علي، أحمد صبري السيد (العتبة العباسية المقدسة - المركز الاسلامي للدراسات الاستراتيجية, 2017)
It was not a surprise of the orientalists to seek for an attempt to discover the reasons of the ascension of Islamic Sufism/ mysticism in addition to its hegemony over the religious status in the Islamic societies, which was a part of their fundamental project in the course of discovering and dissecting the Islamic societies through reading their history in order to comprehend the influences on the movement of the society and development such as religion, anthropology, and the popular heritages. Based on their historical tendency, the oriental researches generally were satisfied, nonetheless, with the elitist approach of reading history, which would be satisfied with following the conclusions of a historical event, its direct influences, and may be the motives of the event, without discussing the factors that had generated those motives. Furthermore, the oriental vision of Islamic mysticism suffered from several drawbacks that they all agreed on a general rule claiming that the mystic movement is an intruding one in the Islamic society in two aspects: ascension and development without explaining the reasons of its continuation till the moment in all the various Islamic societies from both the cultural and the civilizational viewpoints despite the fact of the change in the cultural circumstances that had supported that spread previously. because the policy of occupation and invasion by force alone did not prove to be a wise policy that could enable the colonialist to accomplish those goals apart from reliance on the weapon of knowledge as well. In the forties of the nineteenth century, some voices of theorists in politics and educators rose and invited to rely on knowledge as a means to tear the nation's unity apart and to disperse its gathering, because they could absolutely recognize that the force of weapons alone would not be enough to weaken the nation and to get the best of its power. For example, the French thinker "Thomassy" calls in his book he published in Morocco in 1842 the French to get ready to know the land of the Moroccan Empire as it is unavoidable for the Empire to be invaded someday. Also, the multiplicity of races in the population of the North African countries as the focal point colonization stressed on by the foreign colonialists in order to dominate them completely. The orientalist "Ladreit de Lacharriére" noted that the colonialists fell behind in working out a division among the people of the colonized region that he said, "They never showed any concern aiming at diversifying the racial factors that usually comprise the antagonist population in the hope of searching for cleavage that should be expanded in this population block in order to break it apart." This is exactly what the colonial policy headed for when it focused its concern on the Amazigh (Berber) race, and it tried to make it distinctive from the rest of all other races that form the population map for the occupied countries such as Algeria and Morocco. To clarify the effect of orientalism in the rising of the Amezigh nationality in North Africa, there will be a discussion about this topic in three themes and a conclusion as follows:  Theme One: The Historical Account of the Amezigh Rise Issue  Theme Two: The Forerunners of the Orientalists in North Africa  Theme Three: The Orientalists' Efforts in Theorizing for the Amezigh Nationalism  The Conclusion
Keywords: الفكر الاستشراقى -- الفكر الصوفى -- التصوف الاسلامى -- الفكر الاسلامى